7) Calcule os produtos:
a) (-6y).(-3y) =
b) (+4a²x).(-5ax²) =
c) (+0,5x). +2,4x²) =
d) (-7a).(+ 2ab).(-11a) =
e) (-2xy). (+3x²y).(- ly) =
Respostas
respondido por:
0
A)-18y²
B)-20a³x³
C)1,2x³
D)-154a³b
E)x³y³
respondido por:
1
Resposta:
a) (-6y).(-3y) = 18y^2
b) (+4a²x).(-5ax²) =-20a^3x^3
c) (+0,5x). +2,4x²) =
1,2x^3
d) (-7a).(+ 2ab).(-11a) =
154a^3b
e) (-2xy). (+3x²y).(- ly) =
-6x^3y^3 l
multiplica-se a base e soma-se o expoente
Obs:
(^
elevado)
heriksantos12h:
154ab³?está correto?
Perguntas similares
5 anos atrás
5 anos atrás
7 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás